Altered Light Sensitivity of Circadian Clock in Shank3+/– Mouse - Alamilla, Javier; Ramiro-Cortés, Yazmín; Mejía-López, Adriana; Chavez, José-Luis; Rivera, Dulce Olivia; Felipe, Víctor; Aguilar-Roblero, Raúl (Frontiers in Neuroscience, 2021)
Autism spectrum disorder (ASD) is a neurodevelopmental disorder characterized by impairment in communication and social interaction, repetitive or stereotypical behaviors, altered sensory perception and sleep disorders. In general, the causes of ASD remain unknown, but in Phelan-McDermid Syndrome (PMS) it is known that the disorder is related to the haploinsufficiency of the Shank3 gene. We used an autism model with compromised glutamatergic signaling, the Shank3+/- mouse, to study circadian rhythms architecture of locomotion behavior and its entrainment to light. We also analyzed the synapse between the retinohypothalamic tract (RHT) and the suprachiasmatic nucleus (SCN), employing tract tracing and immunohistochemical techniques. We found that Shank3+/- mice were not impaired in the SCN circadian clock, as indicated by a lack of differences between groups in the circadian architecture in entrained animals to either long or short photoperiods. Similar results were obtained in the re-entrainment to shifts in the Light-Dark cycle and in the entrainment to skeleton photoperiod from DD. However, Shank3+/- mice showed larger phase responses to light pulses, both delays and advances; and rhythm disorganization induced by constant bright light. Immunohistochemical analyses indicated no differences in the RHT projection to the SCN, or the number of SCN neurons expressing the NMDA receptor subunit NR2A; whereas the Shank3+/- animals showed decreased C-Fos induction by brief light pulses at CT22 but increased number of VIP positive neurons. These results indicate alterations in light sensitivity in Shank3+/- mice. Further studies are necessary to understand the mechanisms involved in such increased light-sensitivity, probably involving VIP neurons.